Penggunaan Media Video Canva untuk Mengatasi Kurangnya Kepercayaan Diri Siswa dalam Bertanya, Menjawab, dan Berdiskusi di Kelas III SDN 060791 - Nanda Ramadani; Akbar Nugraha Siagian; Dwisandha Sidauruk; Jerina Basita Situngkir; Lulu Dwi Andani; Stela Lianti Bangun; Sri Charina Sebayang (Jurnal Pendidikan dan Sastra Inggris, 2025)
Student’s lack of confidence in asking, answering, and discussing is one of the obstacles in learning English, especially at the elementary school level. This study aims to analyze the effectiveness of using Canva video-based digital learning media in increasing the confidence of grade III students of SD Negeri 060791. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and document analysis. The results showed that the use of Canva videos was able to create a more interactive learning atmosphere, reduce student’s anxiety, and increase their courage in actively participating in class. In addition, the utilization of this digital media helps students understand the material better and increases their learning motivation. Thus, Canva video-based learning media can be an innovative solution in increasing students confidence in learning English.